Hölderlin and the Pietist Cultural Context - Rodríguez Baigorria, Martín (Revista de Filología Alemana, 2011)
There are relatively few studies focused on the relationship between Hölderlin and the pietist cultural context. However, Württemberg´s historical context offers us a meaningful testimony of these contacts, insofar as it anticipates some of his views in common with this religious tradition. Taking in account the moral dilemmas that arise in this cultural background, it is possible to reconstruct the conflictive beginnings of his poetical vocation, and also, the way his literary imagination recreates these contradictions.